Kelahiran Hak Kebendaan pada Jaminan Fidusia - Supianto, Supianto; Rumawi, Rumawi; Tri Budiman, Nanang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 3 (2024)DO - 10.24843/JMHU.2024.v13.i03.p01, 2024)
The guarantee right owned by the creditor is a material right, which was born not from an obligatoir agreement as contained in Book III of the Civil Code, but born from a material agreement. This study aims to find out what are the characteristics and when material rights in fiduciary guarantees arise or arise as a right that has various privileges. This study uses a normative juridical method with a statutory and conceptual approach. The results of the study show that material rights (zakelijk recht) are rights that give direct power to an object. Material rights that provide guarantees have certain characteristics or characteristics as stated in the Civil Code, including being absolute, which means they can be defended by everyone, being droit de suit, meaning the right to continue to follow the object in the hands of whoever the object is, and being droit de preference, meaning having priority position in paying off receivables. In fiduciary guarantees, the registration stage plays a very important role in the process of giving birth to material rights because the birth of fiduciary guarantees coincides with the recording of fiduciary guarantees in the fiduciary register book. Registration of fiduciary guarantees is intended to strengthen legal certainty and the birth of material rights.